2016
DOI: 10.3389/fimmu.2016.00193
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Free of Control: How Conventional T Cells Overcome Regulatory T Cell Suppression

Abstract: Conventional T (Tcon) cells are crucial in shaping the immune response, whether it is protection against a pathogen, a cytotoxic attack on tumor cells, or an unwanted response to self-antigens in the context of autoimmunity. In each of these immune settings, regulatory T cells (Tregs) can potentially exert control over the Tcon cell response, resulting in either suppression or activation of the Tcon cells. Under physiological conditions, Tcon cells are able to transiently overcome Treg-imposed restraints to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 192 publications
(326 reference statements)
1
69
0
Order By: Relevance
“…This mirrors the phenomena of difficult to cure, long-standing disease that has been described in many different autoimmune diseases of childhood and “autoimmune expansion” may be but one of the underlying mechanisms. 31 To the extent that our “T cell hypothesis” is correct, this would suggest that the failure of 4R+3Dex in these instances may be secondary to lack of anti-T cell agents in this particular combination. The addition of an agent such as mycophenolate mofetil to the 4R+3Dex regimen may contribute to curative therapy in a higher number and broader spectrum of patients.…”
Section: Discussionmentioning
confidence: 91%
“…This mirrors the phenomena of difficult to cure, long-standing disease that has been described in many different autoimmune diseases of childhood and “autoimmune expansion” may be but one of the underlying mechanisms. 31 To the extent that our “T cell hypothesis” is correct, this would suggest that the failure of 4R+3Dex in these instances may be secondary to lack of anti-T cell agents in this particular combination. The addition of an agent such as mycophenolate mofetil to the 4R+3Dex regimen may contribute to curative therapy in a higher number and broader spectrum of patients.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, since the MAPK, AKT, and NF‐κB pathways crosstalk via several molecules, it is possible that PPP1R11 affects joint signaling molecules between the two pathways. Besides, there have been extensive clinical and experimental reports indicating that the MAPK and AKT signaling pathways are involved in inducing T cell resistance to Tregs . In light of these findings, we speculate that targeting these pathways by modulating PPP1R11 may be exploited as a novel therapeutic option for autoimmune diseases in the future.…”
Section: Discussionmentioning
confidence: 81%
“…We and others have shown that Treg‐mediated rapid suppression of T cells is mediated via modulation of NFAT, AP‐1, and/or NF‐κB pathways with differences depending on the particular cell types, stimulation, and readouts used . Furthermore, clinical and experimental studies have reported the involvement of PI3K and protein kinase B (AKT; that are downstream of CD28 signaling) to be involved in inducing resistance in T cells . Given these studies, Tregs seem to affect multiple signaling pathways in target T cells in a context‐dependent manner.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations